EFFECT OF PLANTING METHOD AND ROSE WATER SPRAY ON SEED PRODUCTION IN ONION, (ALLIUM CEPA L.) - Sahaf, F. H. Al- (Emirates Journal of Food and Agriculture, 2017)
Onion (Allium cepa L.) plants of Texas Grano 502, Local Red, and Local White cultivars were grown either from seeds in seed-to-seed method or from sets (bulbil with 1.5-2.0 cm indiameter) in set-to-seed method. The plants were sprayed three times (a week interval) with rose water (contained terpene alcohols) at the stage of opening of 5% of inflorescence flowers during 1997 and 1998 growing seasons. A wide range of insect species visited the umbels of rose water sprayed plants, mainly honeybee (Apis mellifera L.), blowfly (Caliphora vomitoria L.), and housefly (Musca domestica L.), and spraying vegetative part, inflorescence or whole plant revealed similarattractiveness to the insects. Spraying rose water also extended the touch time of the insects on the umbel from 4.5 seconds for untreated to 11.5 seconds for treated plants resulting in a higher percentage of flower set and lower number of aborted flowers in all tested cultivars. Among the plants part treated, the sprayed inflorescence had higher number of seeds (capsule-1) and higherpercentage of seed yield increase (46.1% and 43.8% for Texas Grano 502, 59.5% and 35.6% for Local Red, and 64.8% and 43.1% for Local White cultivars in 1997 and 1998 seasons respectively). A comparison between planting methods, set-to-seed produced greater seed yields compared to seed-to-seed method in all tested cultivars and may be as high as that produced from mother bulb-toseedmethod used by other authors. However, cultivars responded to the rose water spray variably and were affected by planting method. Texas Grano 502 plants had highest seed yield (634 and 1207 Kg. ha-1) when vegetative part in the set-to-seed method was sprayed; whereas spraying the inflorescence in the seed-to-seed method had the greatest seed yield. In Local White cultivar, the highest seed yield (410 and 1199 Kg. ha-1) was achieved when the inflorescence in the set-to-seed plants was treated, whereas, spraying vegetative part with rose water in the seed-to-seed method produced the highest seed yield (359 and 594 Kg. ha-1). Spraying whole plant (1997) or inflorescence (1998) of set-to-seed plants of Local Red had the highest seed yield (890 and 1160 Kg. ha-1 respectively), whereas, in the seed-to-seed method, spraying the vegetative part with rosewater produced more seed yield (562 and 502 Kg. ha-1).